Multimodal Ultrasonic Imaging for Breast Cancer Detection - CAMACHO, Jorge; MEDINA, Luis; CRUZA, Jorge F.; MORENO, Jose M.; FRITSCH, Carlos (Archives of Acoustics, 2012)
Ultrasound is used for breast cancer detection as a technique complementary to mammography, the standard screening method. Current practice is based on reflectivity images obtained with conventional instruments by an operator who positions the ultrasonic transducer by hand over the patient’s body. It is a non-ionizing radiation, pain-free and not expensive technique that provides a higher contrast than mammography to discriminate among fluid-filled cysts and solid masses, especially for dense breast tissue. However, results are quite dependent on the operator’s skills, images are difficult to reproduce, and state-of-the-art instruments have a limited resolution and contrast to show micro-calcifications and to discriminate between lesions and the surrounding tissue. In spite of their advantages, these factors have precluded the use of ultrasound for screening. This work approaches the ultrasound-based early detection of breast cancer with a different concept. A ring array with many elements to cover 360◦ around a hanging breast allows obtaining repeatable and operator-independent coronal slice images. Such an arrangement is well suited for multi-modal imaging that includes reflectivity, compounded, tomography, and phase coherence images for increased specificity in breast cancer detection. Preliminary work carried out with a mechanical emulation of the ring array and a standard breast phantom shows a high resolution and contrast, with an artifact-free capability provided by phase coherence processing.